Pemanfaatan Limbah Pertanian sebagai Pakan Ternak Berkualitas dengan Penerapan Teknologi Fermentasi di Desa Kapedi Kecamatan Bluto Kabupaten Sumenep - Hopid Hopid; Sindi Arista Rahman; Ribut Santosa; Amir Hamzah; Purwati Ratna Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2025)
An educational activity on the use of agricultural waste as animal feed through fermentation technology was held in Kapedi Village, Bluto Subdistrict, Sumenep Regency. The aim of this activity was to improve farmers' understanding and skills in processing agricultural waste, such as rice straw and corn cobs, into alternative feed that is highly nutritious and environmentally friendly. The methods used included interactive extension, practical fermentation feed production, discussion, and evaluation. The results showed high enthusiasm among participants, increased knowledge about fermentation technology, and successful production of fermented feed that was liked by livestock and had the potential to increase productivity. The main obstacles, namely limited initial knowledge and the length of fermentation time, could be overcome with technical assistance. This extension not only provides an economical and high-quality livestock feed solution but also supports sustainable agricultural waste management. It is recommended that fermentation materials be facilitated, advanced training be provided, and socialisation be carried out in other villages so that the benefits of this technology can be expanded.